RETRACTED: Evaluating the Potential of Green Synthesized Zinc Oxide Nanoparticles from the Fruit Extracts of Balanites aegyptiaca as an Antimicrobial and Larvicidal Agent - Lawan, Baba Mushemi; Danbature, Wilson Lamayi; Mamza, Umar Tanko (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
This study investigates the antimicrobial and larvicidal potential of green-synthesized zinc oxide nanoparticles (ZnO-NPs) derived from the fruit extract of Balanites aegyptiaca. The synthesized ZnO-NPs were characterized using UV-Visible spectrophotometry, Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and scanning electron microscopy (SEM). Antimicrobial efficacy was assessed against two Gram-positive bacteria (Staphylococcus aureus, Streptococcus pyogenes), two Gram-negative bacteria (Salmonella typhi, Klebsiella pneumoniae), and two fungal species (Candida albicans, Aspergillus niger). At the highest tested concentration (30 µg/mL), the ZnO-NPs exhibited moderate inhibitory activity across all microbial groups. Larvicidal activity was evaluated against Anopheles mosquito larvae at concentrations of 40, 50, and 60 mg/L. The ZnO-NPs achieved 100% mortality in third and fourth instar larvae, with LC₅₀ values ranging from 35.30 to 59.47 mg/L. The results demonstrate the significant dose-dependent antimicrobial and larvicidal effects of ZnO-NPs synthesized from B. aegyptiaca, supporting their potential application in the development of eco-friendly nanobiopesticides and plant-based therapeutic agents.